Decarbonisation of buildings: Insights from across Europe - Baker,W; Acha,S; Jennings,N; Markides,C; Shah,N (The Grantham Institute, 2022)
This report considers four key challenges facing the UK in reducing carbon emissions from its building stock, and shares insights from across Europe that have the potential to help the UK to decarbonise and increase the energy efficiency of its buildings.